Problem Kejiwaan Tokoh Utama dalam Novel Ayahku Bukan Pembohong Karya Tere Liye - Muhammad Fadilah Sidiq (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Based on the formulation of the problem in the study, namely How are the psychological problems that occur in the main character in the novel Ayahku Bukan Pembohong by Tere Liye. The purpose of the study is to describe the psychological problems that occur in the main character in the novel Ayahku Bukan Pembohong by Tere Liye. The type of research used in this study is descriptive qualitative research. The theory in this study uses Segmund Freud's theory, namely using three methods, namely id, ego and super ego. So the object of this study is the novel Ayahku Bukan Pembohong by Tere Liye. This novel has a prominent psychological picture of the main character who faces emotional conflicts continuously. The contents of the novel describe the feelings of regret of the character Dam who hates his father's story. Interestingly, this novel was chosen using personality theory. The main character in this case is threatened because of the anxiety of the subconscious that is contrary to time. This causes psychological behavior.